Transgender stratification economics - Haggar, Robert, author; Vasudevan, Ramaa, advisor; Bernasek, Alexandra, committee member; Fremstad, Anders, committee member; Dockendorff, Kari, committee member (Colorado State University. Libraries, 2024)
This dissertation provides extensive evidence of economic stratification articulated through cisheteropatriarchal power and white supremacy. This evidence is presented through three discrete chapters. Chapter 1: Research on the economic status of transgender status has found that trans* people face pervasive discrimination from both state and non-state actors. This paper builds upon the growing labor-economics of transgender people but breaks with it by considering economic precarity more broadly. By incorporating insights from intersectional theory and Marxian Feminism, this paper seeks to argue that economic marginalization and social oppression reinforce and enable one another. Following the intersectional methods of stratification economics, this paper compares the economic marginality of trans* people to the US population across income distributions and labor force status using the 2015 United States Transgender Survey and the 2015 American Community Survey. Trans* individuals are clustered in precarious labor force statuses which are characterized by low income. This clustering is more pronounced for transgender women, nonbinary people, and racially marginalized people. These transgender individuals, alongside those with disabilities and those who have experienced workplace discrimination due to their gender identity, are far more likely to engage in low-income self-employment, sex work, and illegal employment. Chapter 2: Trans* people are disproportionately poorer than their cisgender counterparts. Due to the financial cost of maintaining residence in housing and the negative effects of not having adequate housing, the relative impoverishment of transgender individuals may influence their ability to afford housing. The US Dept of Housing and Urban Development defines an individual or household as "cost burdened" when they pay more than 30% of their monthly income to cover housing costs. This study will compare the rates of cost burden across the transgender and cisgender populations and across housing types in the US using the Household Pulse Survey. To estimate housing cost burden, I will construct a cost burden variable for each observation by constructing upper and lower bounds of the range within which cost burden, defined as rent cost divided by income, lies. Transgender men allocate 7.9% more of their total income to rent payments, while female "nones" allocate 9.5% more of their total income, compared to cisgender men. The rent premia paid by transgender individuals compared to cisgender men varies conditional on the racial group considered. Increased rent burdens faced by white individuals are lower than that for Black or Hispanic individuals. Chapter 3: Using Phases 3.2-3.5 of the Household Pulse Survey, this paper establishes statistically significant differences in likelihood of Unemployment Insurance utilization between cisgender men and transgender men, transgender women, and individuals assigned male at birth but identifying as not a man, a woman, or transgender. Transgender men and women and individuals assigned male at birth but identifying as not a man, a woman, or transgender are also more likely than cisgender men to live in households where another adult receives Unemployment Insurance income, relative to cisgender men. These results may follow from the interaction between patriarchal breadwinner norms and the structure of unemployment insurance, which undercuts the ability for cisgender women to access unemployment insurance and encourages cisgender men to avoid unemployment. Psychological costs and lower average incomes may discourage trans* individuals from engaging with Unemployment Insurance.